If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 4 = 11 Reorder the terms: 4 + y = 11 Solving 4 + y = 11 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + y = 11 + -4 Combine like terms: 4 + -4 = 0 0 + y = 11 + -4 y = 11 + -4 Combine like terms: 11 + -4 = 7 y = 7 Simplifying y = 7
| 6x^2-49=0 | | -1=-4+3(1+5n) | | -5-3x=18 | | 3x-17=37 | | 3x^2+30x-72=0 | | -19x-24=-5 | | (-4)w-4=8 | | 5x+2y=-12 | | 14+13x=29 | | 4x^2+24x-28=0 | | X-1.2=-4.6 | | x^2=2x*3 | | -7=x+9 | | 2=x+14 | | 3-3=18m-16m | | -5v-4=26 | | 6p-33-59=4 | | 6m+1=33 | | y-8=0 | | 0=-4(y+9) | | -3x+4x=x-1 | | 6-8k=46 | | 2x+6=4x+-2 | | 5k+13=7k+5 | | 6x+123=4x+167 | | 2x+7=-1 | | -18=x+2 | | 2x+38=4x+16 | | 7a+3=-2a+3 | | 5-8k=2k-5 | | 2-n*5=30 | | 2-n=1-7n+6n |